Scopoletin in cassava products as an inhibitor of aflatoxin production - Gnonlonfin, G.J.B.; Adjovi, Y.C.S.; Gbaguidi, F.; Gbenou, J.; Katerere, D.; Brimer, L.; Sanni, A. (Wiley, 2011)
The scopoletin level in a cassava variety from Benin, BEN 86052, and the compounds effect on the growth of an Aspergillus flavus isolate from cassava chips were investigated. The influence on the biosynthesis of aflatoxins was also investigated. Scopoletin was quantified using high performance liquid chromatography. An in vitro test was used to evaluate the inhibitory effects of cassava flour extracts and pure scopoletin on growth and biosynthesis. The A. flavus isolate was genetically characterized to be an aflatoxin producer using polymerase chain reaction. Scopoletin was found in roots and chips with a level ranging from 4.9 to 242.5 mg/kg dry weight. Scopoletin induction was noticed after a peeling and drying process (6 days). Aflatoxin production by a strain of A. flavus holding the cluster Nor1, Omt1 and OmtB responsible for aflatoxin biosynthesis was inhibited by scopoletin and cassava flour at lower concentrations (0.024 mM). Scopoletin could be used on other commodities susceptible to mycotoxin contamination.